Investors’ response on the deviation between quarterly and annual earnings - Saidin, Saidatunur Fauzi; Malek, Mazrah; Ibrahim, Daing Nasir; Kee, Phua Lian (2017)
Despite the benefits of timely information, concerns have been raised on the reliability of the quarterly accounts.The occurrence of deviation between audited annual accounts and cumulative quarterly accounts indicates the misstatements in the latter.This study examines investors’ response towards the occurrence of the deviation.Data is based on 792 listed companies of Bursa Malaysia in 2012.The results of the OLS regression show that the companies without earnings deviation have significantly higher earnings response coefficient than companies experiencing earnings deviation.It is also found that understated quarterly earnings companies have higher earnings response coefficient than overstated companies.Results imply that investors place higher reliability on the quarterly accounts produced by companies without earnings deviation. Higher reliability is placed on the understated quarterly earnings companies as compared to overstated companies.Findings suggest that investors do value the occurrence and types of earnings deviation.Therefore, steps should be taken to overcome the occurrence of deviation.